Assesment and Induction of Variability for Higher Yield and photoinsensivity in Coleus(Coleus Parviflorus Benth) - Mareen Abraham (Department of Plant Breeding and Genetics, College of Horticulture, 2002)
The project entitled "Assessment and induction of variability for higher yield and photoinsensitivity in coleus (Coleus parviflorus Benth)" were carried out in the Department of plant Breeding and Genetics during the period April 1999 to April 2002, with the objective of inducing variability for photoinsensitivity and higher yield through in vivo and in vitro mutagenesis. Three major field experiments were laid out one at Agricultural Research Station, Mannuthy and two experiments at College of Horticulture, Vellanikkara. Among the collected coleus genotypes wide genetic variability for all the observed characters were noticed. Increased harvest index plant", tuber weight plant" and reduced height plant" contributed to tuber yield. Representative genotypes of the ten clusters were subjected to mutagenic treatment. Mutation has changed the plant height, age of tubers and. tubers plant" in coleus genotypes. Selected mutants showed photoinsensitivity to tuberization an acceptable qualitative change. Mutant 131 and mutant 61 were identified as promising photoinsensitive mutants for year round cultivation. One photoinsensitive tissue culture mutant was identified. But these require further evaluation for yield.